Spiritualisme Tasawuf dan Alternatif atas Problematik Modern: Sebuah Penjajakan Awal - Edwin Syarif (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2003)
This paper explores the relationship between Sufi spirituality and modern problem-solving through an initial examination of Sufism's contributions in a contemporary context. Sufism, as the mystical dimension of Islam, offers a profound spiritual approach to addressing various life challenges. In the modern context, where complex issues such as alienation, identity crises, and materialism often disrupt mental and spiritual well-being, Sufi spirituality can provide significant alternatives. The paper investigates the core principles of Sufism, such as the emphasis on closeness to God, purification of the soul, and achieving inner balance, and how these principles can be applied to address various modern problems. Sufism teaches methods for attaining inner peace through spiritual practices such as dhikr (remembrance of God), contemplation, and self-discipline, which can help individuals cope with stress, anxiety, and dissatisfaction commonly experienced in modern life. The paper also highlights practical examples of how Sufi communities around the world have integrated their teachings with contemporary challenges and how they contribute to individual and social well-being. Through an analytical approach and case studies, this paper aims to provide insights into the potential of Sufi spirituality as an effective alternative for addressing modern issues and offers a foundation for further exploration of Sufism’s relevance and application in contemporary contexts.